Telugu diaspora as soft power: mapping media, cultural ties and political economy with homeland. Issue 1 (2nd January 2017) - Murthy, C. S. H. N.
ABSTRACT: The Telugu diaspora, the second largest Indian linguistic diaspora abroad, plays a key role in influencing the political economy of their home States – Andhra Pradesh and Telangana – as well as their host lands. The intentions of post-globalized Telugu diaspora to continue their traditions and cultural ties, through media and fine arts, with their homelands have in fact transformed the Telugu diaspora itself into a potential source for cultural diplomacy between the two lands. The explosion of Telugu media, Tollywood, mobile, Internet and web-sources, increased earnings and currency exchange of dollar have enabled Telugu diaspora establish numerous Telugu associations across the globe for an increased bi-directional cultural flows and investments in their homelands for their rapid growth and development. Grounded in the centre–periphery model of Ghosh-Schellhorn [2006. "Introduction: A Preface to Peripheral Centers, Central Peripheries." In Anglophone India and its Diasporas, edited by M. Ghosh-Schellhorn and V. Alexander, 12–35. Munster: Lit Verlag] along the side of Friedman's tenets of globalization coupled with the definition of 'soft power' [Chitty, N. Forthcoming. "Soft Power, Civic Virtue and World Politics." In Handbook on Soft Power, edited by N. Chitty, G. Rawnsely, J. Simons, and L. Ji. Routledge; Nye, J. Jr. 2004. Soft Power: The Means to Success in World Politics . Public Affairs/Perseus Books Group; Nye, J. Jr. 2011. The Future of Power . Philadelphia, PA: Public Affairs/Perseus Books Group], the present study tends to map not only the bi-directional cultural flows of Telugu diaspora but also show how these flows perpetuated the caste identities, matrimonial relationships, moral and religious anchoring with the homeland. The study hypothesizes that bi-directional cultural flows that subsume media, television and film industry bear a direct relationship with the political economy of homelands. The study further documents that these bi-directional flows have also transformed Telugu diaspora itself into a flagship resource as a 'soft power'.